Refugees in Germany with children still living abroad have lowest life satisfaction - Ludovica Gambaro; Michaela Kreyenfeld; Diana Schacht; C. Katharina Spieß (DIW Weekly Report, 2018)
Family strongly influences personal well-being-especially in the case of refugees, whose family members often remain in their homeland. This report is the first to closely examine the well-being and family structures of refugees who came to Germany between January 2013 and January 2016. It uses data from the IAB-BAMF-SOEP Survey of Refugees in Germany. Among individuals aged between 18 and 49, nine percent have minor children living outside Germany, whereas twelve percent have a husband or wife living abroad. If the nuclear family is living in Germany-which is more often the case for women than men-refugees are measurably more satisfied with their lives. These findings are also confirmed when accounting for other potential factors for well-being. These findings should be given greater consideration-not least in the debate on family reunification-to enable successful migration, integration, and family policies.
Keywords: H31; I31; J12; 330; refugees; family structure; family reunification; children; well-being